2021
DOI: 10.1177/17085381211063316
|View full text |Cite
|
Sign up to set email alerts
|

The impact of obesity on perioperative and postoperative outcomes after elective endovascular abdominal aortic aneurysm repair

Abstract: Background Obesity is a common and growing health problem in vascular surgery patients, as it is in all patient groups. Evidence regarding body mass index (BMI) on endovascular aneurysm repair (EVAR) outcomes is not clear in the literature. We aimed to determine the impact of obesity on perioperative and midterm outcomes of elective EVAR between obese and non-obese patients. Methods Under a retrospective study design, a total of 120 patients (109 males, 11 females, mean age: 74.45 ± 8.59 (53–92 years)) undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(50 reference statements)
2
0
0
Order By: Relevance
“…Protective measures include predicting potential conditions that may increase radiation exposure in the future. Our analysis confirms the findings in the literature regarding BMI being a major factor that leads to a significant increase in radiation exposure [ 19 ]. Sen et al showed an approximately two-fold increase in radiation exposure in patients with a BMI of >30 kg/m 2 compared with patients with a BMI of <30 kg/m 2 during the implantation of custom-made devices for AAA treatment [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Protective measures include predicting potential conditions that may increase radiation exposure in the future. Our analysis confirms the findings in the literature regarding BMI being a major factor that leads to a significant increase in radiation exposure [ 19 ]. Sen et al showed an approximately two-fold increase in radiation exposure in patients with a BMI of >30 kg/m 2 compared with patients with a BMI of <30 kg/m 2 during the implantation of custom-made devices for AAA treatment [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the proportion of patients with a BMI of >30 kg/m 2 in the group with a critical operation time was significantly higher than in the group with a noncritical surgery duration (89% vs. 75%; p < 0.05). This confirms the clinical observations that obesity, as indicated by an increased BMI, is significantly correlated with a longer procedure time [ 19 ]. This could be attributed to the prolonged duration required for creating inguinal access.…”
Section: Discussionsupporting
confidence: 90%